2010
DOI: 10.1262/jrd.10-056t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tumor Necrosis Factor .ALPHA. and Interferon .GAMMA. on the Viability and mRNA Expression of TNF Receptor Type I in Endothelial Cells from the Bovine Corpus Luteum

Abstract: Abstract. The corpus luteum (CL) is mainly composed of luteal steroidogenic cells (LSCs) and luteal endothelial cells (LECs). Cell death of LSCs and LECs is essential for structural luteolysis. Therefore, it is important to understand the mechanisms regulating cell death in both types of luteal cells. We previously reported that a treatment combining tumor necrosis factor α (TNF) and interferon γ (IFNG) induced cell death in LSCs and that LECs express TNF receptor type I (TNFRI). To investigate the mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
(56 reference statements)
1
20
0
Order By: Relevance
“…Furthermore, although type I IFNs, such as IFN α and β, can stimulate necroptosis in cancer cells and macrophages4748, a single treatment with IFNG also did not affect RIPKs mRNA expression in bovine LSCs. IFNG induces expression of TNF superfamily receptors in several cells104950 including bovine LSCs7, and the combination of TNF and IFNG can stimulate acute apoptosis and luteolysis71051. Based on the above findings, we hypothesized that TNF in combination with IFNG can stimulate RIPK-dependent cell death.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Furthermore, although type I IFNs, such as IFN α and β, can stimulate necroptosis in cancer cells and macrophages4748, a single treatment with IFNG also did not affect RIPKs mRNA expression in bovine LSCs. IFNG induces expression of TNF superfamily receptors in several cells104950 including bovine LSCs7, and the combination of TNF and IFNG can stimulate acute apoptosis and luteolysis71051. Based on the above findings, we hypothesized that TNF in combination with IFNG can stimulate RIPK-dependent cell death.…”
Section: Discussionmentioning
confidence: 96%
“…Apoptosis occurs through two main signaling cascades, namely, the extrinsic apoptotic route and intrinsic apoptotic cascade1415. Some studies have revealed that TNF and IFNG strongly stimulate the extrinsic apoptotic route via stimulating several cytokine receptors, such as TNFRI and FAS, in bovine LSCs67910. Furthermore, another major apoptotic pathway, the intrinsic apoptotic cascade, is regulated by members of the Bcl-protein family, which is composed of antiapoptotic ( e.g ., Bcl-2) and proapoptotic ( e.g ., Bax) proteins41552.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations